Applicability of the "constructed model of counseling Filipinos briefly" to high school students - Letargo, Maria Carmina R. (2008)
The study was conducted to determine the applicability of the Constructed Model of Counseling Filipinos Briefly to the purposively selected sophomore students with academic problems of the Diliman Preparatory School in Diliman, Quezon City. The sample were 8 males who have academic problems as referred by their subject teachers and advisers. The instruments used were a pretest/posttest questionnaire and a follow-up questionnaire given after the counseling sessions. Results of the study revealed that to some extent the counseling sessions with the students were able to help them cope with their academic problem as shown in the improvement of their grades. It could be concluded that the Constructed Model of Counseling Filipinos Briefly is applicable to sophomore high school students. It is recommended that more studies using this model be undertaken as it could be an alternative strategy to western approaches, since it was developed with the Filipino traditions and values in mind.
Thesis (M.A. Guidance)--University of the Philippines, Diliman.
Keywords: Counseling in secondary education -- Philippines -- Quezon City; High school students -- Philippines -- Quezon City